2017
DOI: 10.1111/rda.12975
|View full text |Cite
|
Sign up to set email alerts
|

Colostrum yield and litter performance in multiparous sows subjected to farrowing induction

Abstract: The consumption of colostrum at a low level can compromise the survival and growth of piglets. Therefore, this study aimed to evaluate the effect of farrowing induction on colostrum yield, IgG concentration and the survival and performance of piglets until the weaning. Sows of parity 3 to 7 were assigned into two groups: Control (n = 48), sows with spontaneous farrowing; and induction (n = 48), sows induced to farrow on day 114 of gestation with a PGF analogue. Colostrum and blood samples were collected from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Inducing farrowing on day 114 of gestation had no negative effects on the farrowing process or litter characteristics, which is consistent with previous research using different induction protocols ( Otto et al, 2017 ; Vallet and Miles, 2017 ). It is important to note that all farrowings in this study were attended where sows were checked every 30 min and assistance in farrowing provided, resulting in a low incidence of stillbirths.…”
Section: Discussionsupporting
confidence: 91%
“…Inducing farrowing on day 114 of gestation had no negative effects on the farrowing process or litter characteristics, which is consistent with previous research using different induction protocols ( Otto et al, 2017 ; Vallet and Miles, 2017 ). It is important to note that all farrowings in this study were attended where sows were checked every 30 min and assistance in farrowing provided, resulting in a low incidence of stillbirths.…”
Section: Discussionsupporting
confidence: 91%
“…In another study, the proportions of sows needed farrowing assistance were 41.7 %, 53.6 %, and 26.7 % in control, single injection, and double injection of cloprostenol, respectively (Tospitakkul et al, 2019). Many previous studies reported that farrowing induction with cloprostenol did not change farrowing duration, birth interval, and stillbirth rate (Kaoket, 2006;Gunvaldsen et al, 2007;Gaggini et al, 2013;Otto et al, 2017;Vallet and Miles, 2017;Boonraungrod et al, 2018). Ward et al (2019) reported that each farrowing had about 0.8-1.1 dystocia events.…”
Section: Discussionmentioning
confidence: 96%
“…Prostaglandins and its analogues can be used for farrowing induction (Decaluwé et al, 2014;Boonraungrod et al, 2018). Among them, cloprostenol is the most commonly used drug, and when program starts at day 114 of gestation the stillbirth rate (Gunvaldsen et al, 2007;Gaggini et al, 2013;Otto et al, 2017;Vallet and Miles, 2017;Boonrongraud et al, 2018;Tospitakkul et al, 2019), farrowing duration (Kaoket, 2006;Gaggini et al, 2013;Otto et al, 2017;Boonrongraud et al, 2018), and birth interval (Kaoket, 2006;Boonrongraud et al, 2018) are usually found unaltered.…”
Section: Introductionmentioning
confidence: 99%
“…Colostrum collected at the onset of parturition (T0) contained more lactose and less IgA when parturition was induced, whereas colostrum composition at T24 did not differ between sows with natural or induced farrowing (Foisnet et al, 2011). Farrowing induction had no effect on colostral concentrations of IgG (Foisnet et al, 2011;Otto et al, 2017). It is apparent that if farrowing induction is performed not earlier than one day before the expected farrowing date (based on individual monitoring or on the average farrowing date in the herd), no negative impact on colostrum yield is expected.…”
Section: Quesnel and Farmermentioning
confidence: 99%